Sclerotherapy: A conservative approach in the treatment of oral hemangiomas - Harisha Aitha; Jitender Reddy Kubbi; Ramlal Gantala; Navadeepak Kumar Korvipati (Wolters Kluwer Medknow Publications, 2015)
Hemangiomas are one of the most common neoplasms of infancy with an estimated prevalence of 1-3% among neonates and 10% among children of 1 year of age. It has a female predominance and occurs more frequently among Caucasians than other racial groups. Sixty percent of hemangiomas arise in the head and neck. In 80% of cases, hemangiomas occur as single lesions. They are probably developmental rather than neoplastic in origin. Despite their benign origin and behavior, hemangioma in the oral cavity is always of clinical importance to the dental profession and requires appropriate clinical management as sometimes it is associated with complications like bleeding and ulceration. Here, we report a case of hemangioma of tongue treated with sodium tetradecyl sulfate, a sclerosing agent.